Error Analysis in Speaking Skills of the Eleventh Students of High School in Makassar - Rafisa Zakaria; Muliaty Ibrahim; Muhamad Yahrif (DIALEKTIKA: Jurnal Ilmiah Pendidikan Bahasa, Sastra, dan Matematika, 2022)
This study aims at indentifying as well as to investigating the linguistic and non-linguistic errors students made in speaking performance . This research used qualitative research with the results analyzed obtained through interviews and documentation. The prospective subjects of this study was the eleventh graders, with a total of 152 students. The subjects of research were selected by purposive sampling technique in 11 MIPA 3 consisting of 36 students. The results showed that the remaining errors in speaking were caused by linguistic errors: 97 errors in 34 students in vocabulary, 50 errors in 21 students in grammar, and 41 errors in 18 students in pronunciation. In contrast, the non-linguistic errors of 4 students were fear of making mistakes when speaking and lack of confidence. In addition, students made mistakes when speaking in the aspect of fluency:  filled pauses: 96 errors from 28 students, silent pauses had 22 errors from 15 students and 24 errors from 14 students in repetition, and at the level of understanding, there were 10 errors from 7 students.